Grievance Redress Mechanisms in the Public Sector: A Literature Review - Pande, Suchi; Hossain, Naomi (Open Government Partnership and Accountability Research Center, 2022)
Grievance redress mechanisms (GRMs) in the public sector are institutionalized processes designed to enable people to complain about and seek redress for services they rightfully should have received. This paper reviews evidence on GRMs from around the world, focusing on mechanisms attached to public services and programs in the Global South, where they are relatively new and emerging fast. GRMs matter in particular in the Global South because they are increasingly widespread and found in multilateral aid programs, across national governments, within specific programs and services, as well as in the private sector. GRMs are expected to improve public service efficiency, effectiveness, and fairness by giving people a systematic means of seeking redress for governance failures, and they have strong potential to improve accountability to the most excluded and marginalized people, who tend to find it most difficult to make claims on their state. The review includes a simple framework for understanding the key elements of successful GRMs, as identified through the review process. These are: • Citizen capacity to complain • State capacity to respond • Proactive transparency The review concludes with key research questions to improve our understanding of how GRMs work and could be better designed and implemented.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; governance / governação; mecanismos de reclamação / grievance redress mechanisms; ⛔ No DOI found

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

Mozambique Crisis Response Plan 2020 - IOM - International Organisation for Migration (IOM - International Organisation for Migration, 2020)
The overall objective of IOM's strategy is to support displaced persons and other affected populations in Mozambique to build resilience and progress towards sustainable solutions to displacement while ensuring a continuous response to critical humanitarian needs and rapid response capacities in case of a new disaster and crisis. Recovery and resilience in Mozambique will be facilitated through an effective and locally owned framework that addresses the lifesaving and longer-term needs of affected populations. Ultimately, the plan aims at establishing the basis for recovery and crisis prevention in communities and continuing being a key partner of the Government of Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; displaced communities / comunidades deslocadas

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Economic development and institutions – Mozambique at a fork in the road: an institutional diagnostic: Synthesis and policy recommendations - Cruz, Antonio S; Ferreira, Ines A; Flentø, Johnny; Tarp, Finn (Economic development and institutions, 2020)
We now proceed to bringing together the different elements of previous chapters with the aim of presenting the essence of this country study of Mozambique. In the next section, we take stock and revisit our points of departure from Chapters 2 and 3. This background work culminated in the identification of nine thematic areas, subsequently subjected to individual in-depth studies in Chapters 4–12. We outline the core findings from these studies, and present our integrated analysis of key institutional weaknesses. Next, we go a decisive step further, and analyse and discuss their proximate causes and deep factors. We end with a series of ideas for reform, as an input to national reflection, debate, and action.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; ⛔ No DOI found

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

‘Demonstration fields’, anticipation, and contestation: agrarian change and the political economy of development corridors in Eastern Africa - Chome, Ngala; Gonçalves, Euclides; Scoones, Ian; Sulle, Emmanuel (Journal of Eastern African Studies, 2020)
In much of Eastern Africa, the last decade has seen a renewedinterest in spatial development plans that link mineralexploitation, transport infrastructure and agriculturalcommercialisation. While these development corridors haveyielded complex results–even in cases where significantinvestments are yet to happen–much of the existing analysiscontinues to focus on economic and implementation questions,where failures are attributed to inappropriate incentives or lack of‘political will’. Taking a different–political economy–approach,this article examines what actually happens when corridors‘hitthe ground’, with a specific interest to the diverse agriculturalcommercialisation pathways that they induce. Specifically, thearticle introduces and analyses four corridors–LAPSSET in Kenya,Beira and Nacala in Mozambique, and SAGCOT in Tanzania–which are generating‘demonstrationfields’, economies ofanticipation andfields of political contestations respectively, andas a result, creating–or promising to create–diverse pathwaysfor agricultural commercialisation, accumulation anddifferentiation. In sum, the article shows how top-down grand-modernist plans are shaped by local dynamics, in a process thatresults in the transformation of corridors, from exclusivist‘tunnel’visions, to more networked corridors embedded in localeconomies, and shaped by the realities of rural Eastern Africa.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, João, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

Understanding Decentralization in Mozambique with a Ziblatt-Mann Framework - Ferrant, Coline (International Relations, 2018)
In this article, Ferrant examines decentralization reforms in Mozambique since 1994, through an analysis of primary and secondary sources, and a framework that draws from the theses of political scientist Daniel Ziblatt and sociologist Michael Mann.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização; ⛔ No DOI found

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

Challenges and Strategies in Place-Based Multi-Stakeholder Collaboration for Sustainability: Learning from Experiences in the Global South - Ayala-Orozco, Bárbara; Rosell, Julieta A.; Merçon, Juliana; Bueno, Isabel; Alatorre-Frenk, Gerardo; Langle-Flores, Alfonso; Lobato, Anaid (Sustainability, 2018)
Addressing complex environmental problems requires the collaboration of stakeholders with divergent perspectives, a goal that is challenged by diverse factors. Challenges hindering multi-stakeholder collaboration (MSC) for sustainability have previously been addressed in the context of transnational partnerships. However, less is known regarding how place-based MSC operates, especially in the context of the Global South. To contribute to addressing the factors that hinder place-based MSC for sustainability in the Global South, we analyzed 38 MSC projects spanning diverse ecological and social contexts across Mexico. In a series of participatory workshops, 128 stakeholders from academia, government, business, local communities, and civil society organizations discussed factors that hinder place-based MSC and co-constructed strategies to strengthen collaboration. Some challenges coincided with those identified in previous studies (e.g., divergent visions, inadequate project planning), whereas other concerns that have not been commonly regarded as important emerged as crucial obstacles for MSC. We discuss these challenges in the context of areas of limited statehood and point to the traditions of popular education and participatory action research as a source of valuable tools for place-based MSC. We identify strategies capable of addressing diverse challenges, a result that could aid prioritizing resource allocation to strengthen MSC.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; collaboration / colaboração

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Secret security debts devastate economy - Africa Confidential (Africa Confidential, 2016)
As officials count the rising cost of the hidden debts, President Nyusi faces awkward questions from investors and donors. As Mozambique's mountain of dubious debts tops US$2 billion, there are growing calls for a forensic audit and an international police probe into the officials and entities involved in this massive fraud. The deals and loans arranged under President Armando Guebuza, and largely kept secret under his successor Filipe Nyusi, mean that Mozambicans now face the prospect of penury under the yoke of debt repayments on an epic scale. The role of the banks involved in the deals, whose terms were far above market rates, is also attracting regulatory interest and criticism.
Keywords: G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico

Effects of food price shocks on child malnutrition: The Mozambican experience 2008/2009 - Arndt, Channing; Hussain, M. Azhar; Salvucci, Vincenzo; Østerdal, Lars Peter (Elsevier, 2016)
A propitiously timed household survey carried out in Mozambique over the period 2008/ 2009 permits us to study the relationship between shifts in food prices and child nutrition status in a low income setting. We focus on weight-for-height and weight-for-age in different survey quarters characterized by very different food price inflation rates. Using propensity score matching techniques, we find that these nutrition measures, which are sensitive in the short run, improve significantly in the fourth quarter of the survey, when the inflation rate for basic food products is low, compared to the first semester or three quarters, when food price inflation was generally high. The prevalence of underweight, in particular, falls by about 40 percent. We conclude that the best available evidence points to food penury, driven by the food and fuel price crisis combined with a short agricultural production year, as substantially increasing malnutrition amongst under-five children in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde; ⛔ No DOI found

Public Policies and Private Interests: An Analysis from the Nacala Corridor in Mozambique - Garcia, Ana; Kato, Karina; Garcia, Ana; Kato, Karina (Caderno CRH, 2016)
A política externa brasileira, a partir de 2003, apresentou uma notória curva em direção ao aprofundamento e à expansão das relações com outros países e regiões “do Sul global”. Nesse contexto, o continente africano ganhou importância para as relações internacionais do Brasil. O objetivo do artigo é avançar na compreensão da participação do setor empresarial na cooperação brasileira em Moçambique. Os resultados demonstram que as empresas e seus projetos privados se mesclam nos territórios. Examinaremos o caso do corredor logístico de Nacala, interseção das principais e maiores iniciativas de cooperação e de investimento de empresas brasileiras em Moçambique. O cenário construído nos mostra um tabuleiro no qual a cooperação Sul-Sul e, dentro dela, a cooperação brasileira, não podem ser compreendidas sem serem considerados sua relação com os interesses e investimentos empresariais, o jogo de poder com outros países e as políticas de instituições multilaterais como o Banco Mundial.
Keywords: G - Mozambique / Moçambique; L - english / inglês; infrastructure / infrastrutura; south-south cooperation / cooperação sul-sul

FIFTY YEARS OF TRADE POLICY IN INDONESIA: NEW WORLD TRADE, OLD TREATMENTS - Pangestu, Mari; Rahardja, Sjamsu; Ing, Lili Yan (Bulletin of Indonesian Economic Studies, 2015)
Indonesia's trade policy has evolved over the last 50 years. It has been influenced by the country's level of development and the conflict between openness and protectionism; external developments, such as commodity booms and busts and increased competition; and international commitments, whether multilateral or regional. As a result, trade policy has often been ambivalent and ineffective. Given that Indonesia has undergone various transformations and that the world is a different place from what it was in 1965, the country needs to take a more pragmatic and forward-looking stance. Trade policy needs to be part of a comprehensive strategy to improve competitiveness and diversify exports. If Indonesia is to be part of the new paradigm, where the production of goods and services is based on production networks and global value chains, its policy focus will need to shift from protecting and favouring sectors to promoting trade and industrial policies that encourage the flow of goods, services, and people.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

When do relative prices matter for measuring income inequality? The case of food prices in Mozambique - Jones, Sam; Salvucci, Vincenzo; Arndt, Channing (The Journal of Economic Inequality, 2015)
Changes in relative prices of commodities consumed in different shares across income groups can be expected to alter real income differentials between these groups. Using Mozambican household budget survey and price data from 2002/03 and 2008/09, we show that once relative price increases are accounted for, inequality of real consumption increases substantially. We obtain this result by constructing a price deflator that reflects divergent price dynamics of different product categories. Since the main factors driving this result prevail in other developing countries, it is likely that inequality may be underestimated elsewhere.
Keywords: G - Mozambique / Moçambique; L - english / inglês; income inequality

Learning from citizen participation for accountability in Nampula province - Lopez-Franco, Erika (IDS, 2015)
The Citizen Engagement Program (CEP) in Mozambique is an empowerment and accountability program aiming to improve the quality of health and education services through supporting citizens to monitor them. The program supports citizens to engage with service providers to address identified problems; it also aims to generate evidence for policy and program improvement at the local and national levels. This case study is structured in three main sections. The first section provides a background to set the context in which organizations such as Facilidade emerged across Mozambique, with reference to the ‘third generation’ of decentralization policies in Sub-Saharan Africa and the growing expectation over nearly two decades of ‘participation’ as a magic bullet to improve service-delivery and governance. As well, this section will give an overview of the methodology, some of the assumptions behind the approach and the challenges and questions that the process raised. The second section presents the findings of the research. These are structured around four themes: practices of participation; citizenship building for accountability; inclusion challenges; and other positive outcomes from the work with citizens. Finally, the third section provides conclusions and spells out questions that remain after this exercise. These questions will be useful for CEP, as well as other social accountability initiatives, to bear in mind when thinking about citizen participation for accountability.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; ⛔ No DOI found

Natural Gas and Socio-Economic Transformation in Mozambique: Some Preliminary Evidence - Uetela, Pedro; Obeng-Odoom, Franklin (The Journal of Energy and Development, 2015)
The aim of this article is to extend the state of analysis on the impacts of gas development in Mozambique by evaluating the relationship between the gas sector, the Mozambican economy, and social change. As the resource curse framework is only limited to economic growth, this work utilizes two alternative frameworks—the Staples approach and the Linkages approach—that are melded into an institutional analysis, looking simultaneously at “benefits, costs, and uncertainties” or “blessings, uncertainties, and curses,” and used to conceptualize progress more widely to include not only growth, but other externalities and broader social change as applied to the case of Mozambique. In so doing, the evidence suggests that the natural gas industry in Mozambique has contributed to both the expansion in economic growth and social change. However, the positive experience with social change arises from direct intervention and not necessarily the result of the related economic growth. Indeed, in the process of economic growth, the production and export of natural gas in Mozambique have raised the possibility of major socio-economic and ecological dangers. Contrary to the theoretical criticism of spending windfall revenues on social services as wasteful, we argue that only strategic social and ecological expenditures of gas revenues can provide and increase the chances of the gas industry becoming transformational economically, socially, and ecologically. The article is organized as follows; the next section deals with conceptualizing the paper and describing the sources of data. This is followed by sections that present the results, a discussion of those results, and conclusions and policy implications from the study.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Higher fuel and food prices: impacts and responses for Mozambique - Arndt, Channing; Maximiano, Nelson; Thurlow, James T.; Nucifora, Antonio M. D. (Agricultural Economics, 2008)
Rising world prices for fuel and food represent a negative terms-of-trade shock for Mozambique. The impacts of these price rises are analyzed using various approaches. Detailed price data show that the world price increases are being transmitted to domestic prices. Short-run net benefit ratio analysis indicates that urban households and households in the southern region are more vulnerable to food price increases. Rural households, particularly in the North and Center, often benefit from being in a net seller position. Longer-term analysis using a computable general equilibrium (CGE) model of Mozambique indicates that the fuel price shock dominates rising food prices from both macroeconomic and poverty perspectives. Again, negative impacts are larger in urban areas. The importance of agricultural production response in general and export response in particular is highlighted. Policy analysis reveals difficult trade-offs between short-run mitigation and long-run growth. Improved agricultural productivity has powerful positive impacts, but remains difficult to achieve and may not address the immediate impacts of higher prices.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

Mineral Resources Potential in Mozambique - Lehto, Tapio; Gonçalves, Reinaldo (Geological Survey of Finland, 2008)
The metallic mineral, industrial mineral and construction material resources in Mozambique have been mapped as part of the Mineral Resources Management Capacity Building Project, financed by a grant provided by the Nordic Development Fund. A database covering the location and characteristics of more than 600 mineral indications, showings and deposits within the geographical contract area assigned to the GTK Consortium was created. A total of 140 mineral occurrences were selected for field surveys and assessments that were mainly carried out during May-November 2003, 2004 and 2005. All available data in the report archives of the client, the National Directorate of Geology (DNG), was collected and transferred to the mineral occurrence database, which was then updated with information from field surveys and with new data published by exploration and mining companies on the Internet. New mineral resources maps at the scales 1:50 000 (part of contract area), 1:250 000 and 1:1 million were prepared with the corresponding symbols for various commodities plotted. Favourability maps showing zones with high potential for selected commodities were compiled at the 1:250 000 scale. The mineral resources in Mozambique were described in the four map explanation volumes and summarized in the final reports for the projects Geological Mapping LOT 2 and Geological Mapping LOT 3. As a consequence of increased geological knowledge, facilitated by the activities of the GTK Consortium, investments in Mozambique’s mineral potential by leading international and regional mining companies is already increasing. Currently, global mining houses are investing in exploration for energy minerals (hydrocarbons, coal and uranium), for titanium and zirconium in heavy mineral sands, for gold and gemstones, for the agricultural minerals lime and phosphate and for tantalum, fluorite and other industrial minerals.
Keywords: G - Mozambique / Moçambique; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; ⛔ No DOI found

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Eight Years of Multiparty Democracy in Mozambique: The Public’s View - João Pereira; Ines Raimundo; Annie Chikwanha; Alda Saute; Robert Mattes (Afrobarometer Working Papers, 2003)
Since its emergence from a brutal, 17-year civil war, Mozambique’s process of political reform has faced a number of challenges. The first has been to empower ordinary Mozambicans by allowing them to participate in a democratic system and enabling them to voice their demands to the state and hold it accountable. The second has been to rebuild a state with the capacity to respond to citizen demands effectively. And given the long history of violent division, a third challenge has been to build a state that enjoys broad legitimacy – a legitimacy that spans the bitter partisan divides of the past, enabling the formation of a strong, authoritative state with the ability to enforce the rule of law, but also the discipline to rule through transparent procedures. Perhaps the best evidence by which to judge the success of the process of political reform are the opinions of ordinary Mozambicans. Rather than looking to expert judgments or to measures of formal constitutional rights, we believe that the views of ordinary citizens – as the ultimate consumers of what democratic governments supply – can offer perhaps the most conclusive assessment of the quality of governance. What do they say? Through its partner in Mozambique, the Public Opinion Service of the Centre for Population Studies at the University of Eduardo Mondlane, the Afrobarometer surveyed a nationally representative sample of 1425 Mozambicans citizens, aged 18 years and older, using a multi-stage, area-stratified, clustered sample designed by the National Institute for Statistics. The survey was carried out between August and October 2002 in all 10 provinces of the Republic of Mozambique. At a confidence level of 95 percent, a sample of this size allows a confidence interval, or margin of error, of plus or minus 2.5 percent. This means that, had we interviewed every Mozambican, 19 times out of 20 the results would differ from those of this survey by no more than 2.5 percent. The evidence from this survey suggests that although Mozambique is plagued by what appear to be insurmountable problems, in general the country appears to be on the right path as an emerging democracy. While the society faces vast challenges of building human and social capital to empower citizens further and increase the capacity of the state, the democratization that has occurred since Mozambique opened its political space has gone a long way in propelling democracy forward.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; accountability / responsabilização; civil society / sociedade civil

Endangering safe motherhood in Mozambique: prenatal care as pregnancy risk - Chapman, Rachel R. (Social Science & Medicine, 2003)
Despite high infant and maternal mortality rates, many Mozambican women with access to prenatal services delay prenatal clinic consultations, limiting opportunity for prevention and treatment of preventable pregnancy complications. Ethnographic research, interviews with health providers and longitudinal pregnancy case studies with 83 women were conducted in Central Mozambique to examine pregnant women's underutilization of clinic-based prenatal services. The study found that pregnancy beliefs and prenatal practices reflect women's attempts to influence reproduction under conditions of vulnerability at multiple levels. Women reported high maternal reproductive morbidity, frequent pregnancy wastage, and immense pressure to bear children throughout their reproductive years. Reproductive vulnerability is intensified by poverty and an intense burden placed on poor, peri-urban women farmers for family subsistence and continuous fertility in a period of economic austerity, land shortages, and increasing social conflict and inequality. In this environment of economic insecurity exacerbated by congested living conditions, women report competing for scarce resources, including male support and income. This vulnerability heightens women's perceptions that they and their unborn infants will be targets of witchcraft or sorcery by jealous neighbors and kin. They respond by hiding pregnancy and delaying prenatal care. Within the context of women's perceived reproductive risks, delayed prenatal care can be seen as a strategy to protect pregnancy from purposeful human and spirit harm. Women mobilized limited resources to acquire prenatal care outside the formal clinic setting. It is concluded that provision of clinical prenatal services is insufficient to reduce reproductive risks for the most socially and economically marginal since it is their vulnerability that prevents women from using available services. Confidential maternity services and social safety nets for greater economic security are recommended.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil

A study of the actual and potential usage of information and communication technology at district and provincial levels in Mozambique with a focus on the health sector - Braa, Jørn; Macome, Esselina; Mavimbe, João Carlos; Nhampossa, José Leopoldo; da Costa, João Leopoldo; José, Bonifacio; Manave, Aurélia; Sitói, António (The Electronic Journal of Information Systems in Developing Countries, 2001)
This article presents results from a study on the use and appropriation of information and communication technologies (ICT) in Mozambique with a focus on the health sector. The three provinces of Gaza, Inhambane and Niassa were surveyed and two questionnaires addressing 1) computer users and their ability to manage ICT, and 2) health workers and their handling of health information, were used. Based on this study appropriate strategies for developing an ICT-infrastructure with the needs of the health sector as points of departure are discussed. The study is born out of a program to strengthen and further develop the health information and management systems at district and provincial levels as part of a process to support decentralisation of the health system in Mozambique. The study shows that computers and Internet are rapidly being spread to the provincial capitals and major districts in Mozambique. A main problem identified is the lack of ICT-skills and education and poorly developed infrastructure and networks of support. There are very few formal ICT companies providing hardware, and even less, software support. Maintenance and learning about ICT are to a large extent going on within informal networks of computer users in the provinces. A main finding in this study is that development of ICT capacity and information systems at district and provincial levels in Mozambique needs to be an integrated effort across sectors. A district health information system cannot be developed in a void. A general recommendation is to develop educational programmes ranging from training of ICT entrepreneurs and health workers and managers, to Masters and PhD programmes in ICT and health information systems. A specific recommendation related to health information systems development is to focus on the district level and to develop a strategy which encompasses and integrates all districts, both the advanced districts with computers and the majority of the districts where there are no computers.
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health - health information systems / saúde - sistema de informação de saúde; health / saúde

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Introduction: Accountability through Participation: Developing Workable Partnership Models in the Health Sector - Cornwall, Andrea; Lucas, Henry; Pasteur, Kath (IDS Bulletin, 2000)
The IDS Participation and Health and Social Change Groups convened a workshop in October 1999 to share experience with the use of participatory approaches in enhancing accountability in the health sector, and to explore some of these challenges. The articles in this bulletin reflect some of the richness of experience on the ground in building effective participation, as well as some of the many issues that arise in moving towards more active citizen engagement with service provision. They bring experience from current and ongoing work to reflect on the links between participation, accountability and improvements in health. The workshop explicitly aimed to reflect on experiences that were moderately successful, in order to identify potential elements that contribute to and impede the success of efforts to build accountability through participation. It is important to emphasise that understanding of the complexities of this approach is at a very early stage. The design of interventions is complex and often highly contextdependent. Rather than attempt to establish any blueprint for future activities, the workshop sought to explore the issues and attempt to advance the debate. In this introduction we draw out some of the principal themes emerging from the articles included here, and from workshop discussions.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health / saúde

'Dhlakama É Maningue Nice!': An Atypical Former Guerrilla in the Mozambican Electoral Campaign - Cahen, M. (Transformation, 1998)
Despite significant problems with urban criminal gangs and highway robbers, Mozambique is a country at peace since 4 October, 1992. Under the auspices of the Italian religious congregation of Santo Egidio,4 Joaquim Alberto Chissano, president of the Republic and of the Frente de libertagao de Mozambique (FRELIMO), once the 'Marxist-Leninist' single-party of the country, and Afonso Dhlakama, president of the Resistencia national de Mogambique (RENAMO), the former guerrilla group and longtime recipient of aid from South Africa, signed the 'General Peace Accord' on that date. This agreement has never seriously been called into question. During the first 15 days following the accord there were a number of incidents. For example, it contained provisions for maintaining each party's administration in their part of the country, but did not specify the zones belonging to one party or the other. As a result, a number of RENAMO regional commanders sought to occupy areas that they had not previously controlled, the largest one being Angoche in Zambezia. It appears that they had told Afonso Dhlakama that they already held these areas, and following the peace accords, they urgently sought to gain real possession of the territory in question.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict / conflito; ⛔ No DOI found

Women in Mozambique: Gender Struggle and Gender Politics - Arnfred, Signe (Review of African Political Economy, 1988)
The liberation of women is a fundamental necessity for the revolution, a guarantee of its continuity and a condition for its success (Machel, 1973). In his opening address to the first conference of the Mozambique Women's Organisation (OMM) in 1973, Samora Machel, President of Frelimo, affirmed that women's emancipation was an integral aspect of revolutionary struggle. In 1973 Frelimo was still a liberation front engaged in armed struggle against colonial rule. The northern part of Mozambique was a battle ground and the first OMM conference had to be held in the Frelimo camp at Tunduru in southern Tanzania. In the OMM's present national. secretariat in Maputo, a photograph of the participants of this first conference can be seen. Peasant women and women guerilla's are lined up outside the meeting hut, amongst them Samora Machel in battledress. The non-hierarchical atmosphere depicted in this photograph is in marked contrast to the more formal arrangements on similar later occasions. The participation of women in the war was massive. In 1967, at the request of women themselves, a women's detachment of the guerilla army - Destacamento Feminino - had been formed. Part of its task was to inform and mobilise the peasant population. To support this work, a broader non-military organisation of women was needed. This was the origin of the foundation of the OMM in 1973.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; gender / género

Ethnicity, Politics, and History in Mozambique - Alpers, Edward A. (Indiana University Press, 1974)
Conclusion Of course, the political disgrace of Joana Simiao does not by itself solve the problem of Makua-Lomwe separatism, any more than the collapse of the Movement for a Free Mozambique has solved the larger problems of national reconstruction in Mozambique. But by now it should be clear to all that the only political movement qualified to achieve that goal is FRELIMO, who demonstrably are working for the interests of all Mozambicans and who enjoy the support of Mozambicans of all races, religions, and ethnic backgrounds, including both Makua-Lomwe and Maconde. During its decade of armed struggle FRELIMO has successfully defended its just cause against attack from without and dissension from within. In the process it has painstakingly built a truly national liberation movement. The lessons learned in that crucible, which se suddenly belongs to the past, must now be applied to the future
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; politics / política; ⛔ No DOI found